ANALISA DAN PERANCANGAN SISTEM INFORMASI PURCHASE ORDER PADA PT. NIKOMAS GEMILANG - Ahmad Rufai; Budi Pangestu (Amal Insani Foundation, 2022)
The purpose of this paper is to analyze the information system Purchase Order and coding of materials at PT. Nikomas Gemilang Serang Banten and ongoing production of draft Purchase Order information system and a material code on PT. Nikomas Gemilang Serang Banten. The method used to analyze the information system Purchase Order and coding of materials at PT. Nikomas Serang Banten using PIECES (Performance, Information, Economic, Control, Efficiency, and Service). While the system design method used is the Logical Model (modeling logic) by making use traditional models Logical DFD (Data Flow Diagram / Data Flow Diagram), Diagram Context, Overview Diagram, and Detailed Diagram. Data Flow Diagram of the proposed illustrates the flow of data processed by the system, the system can provide the option transaction and can generate output reports are required. The design of the proposed system on information systems Purchase order and coding material that the system can display the selection of the type of the required fields, and can generate output reports transactions.